Enhancement of polyunsaturated fatty acid production under low-temperature stress in Cylindrotheca closterium - Almeyda, María Delfina (2020)
Marine microalgae synthetize great amounts of essential metabolites such as fatty acids and amino acids. In addition, their exposure to stress factors can induce the overproduction of these desirable metabolites. Thus, in this work, we assessed the effect of low-temperature stress on lipid production and composition of the diatom Cylindrotheca closterium, in order to evaluate its potential as an alternative feedstock of essential polyunsaturated fatty acids (PUFAs). The alga was first cultured in a photobioreactor at 20 °C (control), and stressed by suddenly lowering the culture temperature, from 20 °C to 11 °C, at the exponential (LTEP) or stationary (LTSP) growth phases. Neutral lipids (NLs) were the main lipid fraction of all conditions assayed, and their production was maximal at LTSP. Fatty acid analysis also showed that the greatest production of PUFAs was observed in the NL fraction at LTSP condition. In terms of essential fatty acids, the production of the omega-3 fatty acids eicosapentaenoic acid and docosahexaenoic acid was similar in both treatments. The production of omega-6 fatty acids was significantly higher in the LTSP condition due to an increase in arachidonic acid content. Sterols increased under both stress conditions, with a predominance of cholesterol. Considering that the LTSP condition elicited the best PUFA production, the amino acid composition was determined. The 46.81% of total amino acids were essential components for aquatic animals. These findings provide evidence of the potential of C. closterium as an alternative, sustainable source of sterols, essential fatty acids, and amino acids.